2005
DOI: 10.1021/bi051282o
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Product Feedback Regulation and Drug Resistance in Cytidine Triphosphate Synthetases from the Structure of a CTP-Inhibited Complex,

Abstract: Cytidine triphosphate synthetases (CTPSs) synthesize CTP and regulate its intracellular concentration through direct interactions with the four ribonucleotide triphosphates. In particular, CTP product is a feedback inhibitor that competes with UTP substrate. Selected CTPS mutations that impart resistance to pyrimidine antimetabolite inhibitors also relieve CTP inhibition and cause a dramatic increase in intracellular CTP concentration, indicating that the drugs act by binding to the CTP inhibitory site. Resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
108
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(120 citation statements)
references
References 61 publications
12
108
0
Order By: Relevance
“…For example, the enzyme has two overlapping binding sites for UTP and CTP (9). This arrangement permits the spontaneous development of resistance to drugs such as cyclopentenylcytosine and release from feedback inhibition by CTP (45-48) through clustered CTPS gene mutations altering residues in the CTP-binding site while retaining the ability of CTPS to bind UTP and catalyze CTP formation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the enzyme has two overlapping binding sites for UTP and CTP (9). This arrangement permits the spontaneous development of resistance to drugs such as cyclopentenylcytosine and release from feedback inhibition by CTP (45-48) through clustered CTPS gene mutations altering residues in the CTP-binding site while retaining the ability of CTPS to bind UTP and catalyze CTP formation.…”
Section: Resultsmentioning
confidence: 99%
“…The detailed mechanism by which GTP induces the conformational changes to activate the glutaminase activity and inhibit NH 3 -dependent CTP formation remains unknown despite the recent solution of the structures of apo-E. coli CTPS (no nucleotides bound) (3), E. coli CTPS with bound CTP and ADP (9), and Thermus thermophilus CTPS with bound glutamine (23). Although Baldwin and co-workers (3) crystallized E. coli CTPS in the presence of GTP, no GTP was bound in the crystalline enzyme.…”
mentioning
confidence: 99%
“…The CTP product provides a negative feedback by competitively inhibiting the UTP substrate [10,15,[20][21][22][23]. Despite bacterial and mammalian lineages having diverged approximately three billion years ago [24], their CTP synthase molecules Filament-formation appears to be a conserved, and thus an essential, property of CTP synthases.…”
Section: How Is the Cytoophidium Assembled?mentioning
confidence: 99%
“…Biochemical studies have shown that CTP synthase can form inactive dimers and active tetramers [13]. Polymerisation of CTP synthase could result from conformational changes induced by binding to various ligands [15,16,23]. Polymerisation of CTP synthase into filamentary structures might stabilise the enzyme in a particular state, whether active, inactive or a mixture of both.…”
Section: How Is the Cytoophidium Assembled?mentioning
confidence: 99%
“…All CTP synthetases identified from bacteria, parasites, yeast and mammals contain conserved CTP synthetase and glutamine amide transfer domains that are involved in catalysis (Fig. 3) [28][29][30][33][34][35][36][37][38][39]. The analysis of the Escherichia coli structure has shown that CTP synthetase has a novel product inhibition mechanism in which shared substrate and product moieties bind to a single subsite while specificity is conferred by separate sites [34].…”
Section: Ctp Synthetases Of S Cerevisiaementioning
confidence: 99%